1999
DOI: 10.2331/fishsci.65.700
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Morphological Development of Laboratory-Reared Yellowfin Tuna <i>Thunnus albacares</i> Larvae and Early Juveniles, with Special Emphasis on the Digestive System

Abstract: Yellowfin tuna Thunnus albacares larvae were reared from hatching beyond metamorphosis in May and June 1996. The larval size was 2.65mm SL at just after hatching and 27.68mm SL on Day 37. Transformation to juveniles occurred around 30 days after hatching at about 13mm SL. The larvae ini tially fed on rotifers since Day 4, on fish larvae and Artemia nauplii since Day 16, and then on frozen fish and minced fish meat. The primitive digestive system differentiated on Day 4. The gastric gland and pyloric caeca firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 5 publications
4
34
0
1
Order By: Relevance
“…In studies focusing on the analysis of nutritional status of tuna larvae, the existing techniques have tended towards histological methods, mainly focusing on histological characteristics and appearance of the digestive tract (Margulies, 1993;Kaji et al, 1996Kaji et al, , 1999. However, nutritional condition studies by nucleic acid and protein content estimation are practically lacking in larval tuna.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In studies focusing on the analysis of nutritional status of tuna larvae, the existing techniques have tended towards histological methods, mainly focusing on histological characteristics and appearance of the digestive tract (Margulies, 1993;Kaji et al, 1996Kaji et al, , 1999. However, nutritional condition studies by nucleic acid and protein content estimation are practically lacking in larval tuna.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have used histological methods to track the nutritional status of tuna larvae (Margulies, 1993;Kaji et al, 1996Kaji et al, , 1999. The only study in which nucleic acid and protein content was analysed refers to the species T. maccoyi (Carter et al, 1998), for which the differences of specific growth rates and nutritional status in farmed juveniles subject to diet variations were assessed.…”
Section: Introductionmentioning
confidence: 99%
“…This precocious timing of digestive system differentiation in scombrids may suggest an adaptation allowing the early appearance of piscivorous habits and high growth rates during the early life stages. Changing the feeding schedule from invertebrate zooplankton to fish larvae (see section 4.2.1) is therefore associated with the functional development of the digestive system and seems to be reasonably effective in the rearing of Thunnus larvae (Kaji et al, 1999). These studies on the development of digestive capacity of larval and juvenile tunas have shown that, after commencing feeding, trypsin-like and amylase-like activities increased as larvae grew, and pepsin-like activity increased and stomach and pyloric caeca functions developed from the post-flexion phase to juvenile transition (Miyashita et al, 1998;Kaji, 2002).…”
Section: Early Digestive Capabilitiesmentioning
confidence: 99%
“…Most marine fish larvae have poorly developed digestive systems at first feeding (Sargent et al, 2002), although the larval type-gut has a considerable processing capacity that can support high growth rates, and the adult-type of digestive system (including a functional acid-producing stomach) only develops at metamorphosis, weeks to months after first feeding. However, several studies have revealed that in scombrid larvae such as Spanish mackerel (Scomberomerus niphonius), chub mackerel (Scomber japonicus) and striped bonito (Sarda orientalis), and also NBT and YFT, the adult-type digestive system is established at the mid phase of the larval period or around the first feeding stage, during scombriform-type metamorphosis (Kaji et al, 1996;Miyashita et al, 1998;Kaji et al, 1999;Kaji, 2002;Kaji et al, 2002). Moreover, and in contrast to straight gut teleost fish larvae, bluefin tuna present a rotated gut, which permits retention of ingested food for some time in the anterior midgut, and retrograde peristalsis as a mechanism for filling the pyloric caeca .…”
Section: Early Digestive Capabilitiesmentioning
confidence: 99%
“…Kaji et al, 1999;Govoni et al, 2003) is another area for fruitful research that will aid in the resolution of growth and mortality.…”
Section: Insight Nd Outlookmentioning
confidence: 99%